Applying Using Structural-Parametric Geometric Models for Rational Design of Technological Processes in Mechanical Engineering - Virchenko, Gennadii; Martynov, Viacheslav; Sergeychuk, Oleg; Usenko, Valery (International Journal of Engineering and Technology, 2018)
The article is devoted to some questions of applying the methodology of structural-parametric geometric modeling in modern machine building. Theoretical and practical relevance of the mentioned scientific-applied theme has been substantiated. The main purpose of this publication is to describe the basic provisions of the proposed method of rational computer design of groups of technical objects and the design of technological processes of their production. The corresponding examples of practical use of the considered modeling techniques concerning mechanical parts manufactured by cutting are presented and analyzed. The main advantages of these techniques have been substantiated in comparison with the existing traditional methods of designing technological processes in mechanical engineering. The basic prospective directions of carrying out further scientific researches concerning the outlined subjects have been determined.